Normative nasalance scores for brazilian Portuguese using new speech stimuli - Marino, Viviane Cristina De Castro [UNESP] (2016)
Objective: Normative data were established for newly developed speech materials for nasalance assessment in Brazilian Portuguese. Materials and Methods: Nasalance scores of preexisting passages (oral ZOO-BR, low-pressure oral ZOO-BR2 and NASAL-BR), new nasalance passages (oral Dudu no zoológico, oral Dudu no bosque, oral-nasal O cãozinho Totó and nasal O nenê) and Brasilcleft articulation screening sentences were collected from 245 speakers of Brazilian Portuguese, including 121 males and 124 females, divided into 4 groups: children (5-9 years), adolescents (10-19 years), young adults (20-24 years) and adults (25-35 years). Results: Across all nasalance passages, adult females scored on average 2 percentage points higher than males. Children scored 2-4 percentage points lower than older groups for the preexisting nasalance passages ZOO-BR and ZOO-BR2. Nasalance scores for the new nasalance passages were not significantly different from the preexisting passages. Scores for high-pressure sentences did not differ significantly from the oral nasalance passage Dudu no bosque. Conclusion: The nasalance scores for the new nasalance passages were equivalent to the preexisting materials. The new shortened and simplified nasalance passages will be useful for assessing young children. Normative scores for the Brasilcleft high-pressure sentences were equivalent to the new oral passage Dudu no bosque.